ESG CONTROVERSIES ON CORPORATE VALUE AND MARKET RISK: THE MODERATING ROLE OF BOARD INDEPENDENCE - Peter Chinedu Okoye; Fadzlina Mohd Fahmi; Mazurina Mohd Ali (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2025)
This study investigated the impact of ESG controversies on firms’ corporate value and market risk, with a keen interest in the moderating role of board independence. Deploying pooled panel models as earlier adopted by prior studies, the study sampled 117 publicly quoted firms indexed as constituents in FTSE4Good Bursa Malaysia (F4GBM), with ESG controversy scores between the period 2021 to 2023, giving a total of 351 firm-year observations. The findings revealed that the ESG controversy score has an insignificant impact on corporate value, while the ESG combined score, which is the performance score after controversy outlay, had a strong, significant positive impact on corporate value. However, the ESG controversy score was revealed to have a considerable positive impact on market risk, while the ESG combined score showed a significant but inverse effect on market risk. Furthermore, it was revealed that the interaction of board independence and ESG controversy does not have a significant moderating effect on corporate value. In contrast, the interaction of board independence and ESG controversy has a significant moderating effect on firms’ market risk exposure. The study’s findings prompted a couple of substantial contributions relevant to scholarly literature, researchers in ESG disputes, governance practitioners, ESG regulatory policymakers, and company managers. It will enhance understanding within the academic community and facilitate business and regulatory decision-making in the corporate environment.